Unravelling anti-cancer properties of solanaceous extracts using GC–MS and HPLC - Iqra Riaz; Yamin Bibi; Muhammad Arshad; Muhammad Sheeraz Ahmad; Manzer H. Siddiqui; Yawen Zeng; Abdul Qayyum (Scientific Reports)
Abstract Cancer is a complex health issue that today’s medical science is dealing with, which has a mortality rate that is almost identical to that of cardiac disorders. Because of the adverse effects of the majority of the medications used in its therapy, managing it remains a major concern despite the availability of numerous remedies. This article attempts to contribute to the scientific developments in the Solanaceae family’s anti-cancer field. Thus, this study consisted of isolating β-amyrin, cedryl acetate, lupeol, and 2-pentadecanone, 6,10,14-trimethyl from Cestrum aurantiacum to determine the anti-tumor activity. The plant material was dried, pulverized, and small-scale extraction was done. Brine shrimps, cell lines (A549, Hela, HEPG), and Caenorhabditis elegans were used initially to examine three solanaceous plant extracts (Solanum villosum (SV), Cestrum aurantiacum (CA), and Brugmansia suaveolens (BS)). The best results were shown by ethanol extract of Cestrum aurantiacum that why large-scale extraction and GCMS of this extract were done. The antitumor potential can be explained by the presence of β-amyrin, cedryl acetate, lupeol, and 2-pentadecanone, 6,10,14-trimethyl.